(untitled) - Aoki, Masahiko (Oxford, England, 1984)
This highly original book challenges the orthodox economic theory of the firm as a mysterious "black box" whose internal design is unknown and irrelevant and which operates solely to maximize shareholder profit. Instead, the author proposes a new "cooperative game theory," in which the firm is a coalition of shareholders and employees, with its market behavior and internal distribution the result of a cooperative game (bargaining). Aoki tests his model against existing industrial structures, including the Anglo-American unionized firm, the German/Swedish co-determination firm, and the American non-union or Japanese firm.
Keywords: Industrial organization,Business enterprises,Industrial relations,Tổ chức công nghiệp,Doanh nghiệp kinh doanh,Quan hệ công nghiệp; Mathematical models,Mathematical models,Mathematical models,Mô hình toán học,Mô hình toán học,Mô hình toán học